STUDENT OLYMPIAD: PROBLEMS AND PROSPECTS - Igor L. Gonik; Olga V. Yurova; Alexander V. Tekin; Alexander V. Fetisov; Oleg K. Chesnokov (Moscow Polytechnic University, 2016)
The article focuses on the issues of development of the students' Olympiad movement in Russia, in particular, the development of student research competitions in higher school. Concurrently the expansion of Olympiad movement, a list of issues occurring now in national higher education expands too. One of the main problems is the decay of ties of the Olympiad movement with the scientific community, predominance of "Olympiad management" with the corresponding subculture. The authors invite all interested parties to join the discussion about them the topical problems of students' Olympiad movement.